Fundamentals of electric circuits - Alexander, Charles K. (McGraw Hill, 2007)
Aims to present circuit analysis in an easier to understand manner. Here, students are introduced to the six-step problem-solving methodology, and are consistently made to apply and practice these steps in practice problems and homework problems, using the KCIDE for Circuits software.